2018
DOI: 10.1371/journal.pone.0204123
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of early breast cancer patient survival using ensembles of hypoxia signatures

Abstract: BackgroundBiomarkers are a key component of precision medicine. However, full clinical integration of biomarkers has been met with challenges, partly attributed to analytical difficulties. It has been shown that biomarker reproducibility is susceptible to data preprocessing approaches. Here, we systematically evaluated machine-learning ensembles of preprocessing methods as a general strategy to improve biomarker performance for prediction of survival from early breast cancer.ResultsWe risk stratified breast ca… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Inna Y. Gong et al. explored several datasets from GEO database based on four published hypoxia signatures [Buffa ( 12 ), Winter ( 44 ), Hu ( 45 ), and Sorensen ( 46 )], and confirmed to a certain extent that hypoxia-related gene signatures had potential to be used as biomarkers to predict survival of early breast cancer ( 47 ). By contrast, Maud H W Starmans et al.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Inna Y. Gong et al. explored several datasets from GEO database based on four published hypoxia signatures [Buffa ( 12 ), Winter ( 44 ), Hu ( 45 ), and Sorensen ( 46 )], and confirmed to a certain extent that hypoxia-related gene signatures had potential to be used as biomarkers to predict survival of early breast cancer ( 47 ). By contrast, Maud H W Starmans et al.…”
Section: Discussionmentioning
confidence: 97%
“…Enriched studies indicate that hypoxia-related gene signatures generated in vitro and in vivo have prognostic power in breast cancer and other cancers. Inna Y. Gong et al explored several datasets from GEO database based on four published hypoxia signatures [Buffa (12), Winter (44), Hu (45), and Sorensen (46)], and confirmed to a certain extent that hypoxia-related gene signatures had potential to be used as biomarkers to predict survival of early breast cancer (47). By contrast, Maud H W Starmans et al identified 295 up-regulated and 164 downregulated genes under hypoxia in breast (MCF7), colon (HT29) and prostate (DU145) carcinoma cells in vitro, but they found that none of these in vitro derived signatures consisting of hypoxia-induced genes are prognostic when in a much larger cohort of breast cancer patients in vivo (48).…”
Section: Discussionmentioning
confidence: 98%
“…An ensemble of linear classifiers is trained for feature selection and diversity among them is induced by bootstrap resampling. Several authors have applied ensemble methods in feature selection to improve the robustness of the gene markers found ( Abeel et al , 2010 ; Gong et al , 2018 ; Zhao et al , 2011 ). The ensemble of lists is combined by selecting the genes associated to the IHC variables with highest stability.…”
Section: Methodsmentioning
confidence: 99%
“…Within this problem, some integrative approaches attempted to combine protein interactome network information with gene expression data to more accurately predict prognosis ( Das et al , 2015 ). Others are based on ensemble methods ( Abeel et al , 2010 ; Gong et al , 2018 ), that try to reduce the variance of the estimator considering different feature selection algorithms or different preprocessing methods.…”
Section: Introductionmentioning
confidence: 99%
“…For survival analysis, in the R statistical environment, we utilized the Kaplan–Meier Plotter database via the statistical package “survival” to calculate Kaplan–Meier survival curves and the number-at-risk. Furthermore, the hazard ratio (and 95% confidence intervals) and log-rank p were calculated for each gene [ 27 ]. The statistical analysis was considered significant when p < 0.05.…”
Section: Methodsmentioning
confidence: 99%